Ayurvedic management for hypertension with micro albuminuria: a case report - V. S., Renjumol (International Journal Of Community Medicine And Public Health, 2024)
Hypertension is a non-communicable disease in which the pressure of blood pushing against the arterial walls becomes high. In chronic stage it leads to severe systemic diseases, which affects heart, kidney, lung etc. The main causative factors are unhealthy food and lifestyle, stress, smoking, Alcohol, obesity and hereditary. Microalbuminuria in Hypertension is an early sign of kidney damage and is considered as a predictor for the end stage of renal disease and cardiovascular disease. So, it is of great importance to manage microalbuminuria or high urine albumin creatinine ratio and progression of kidney disease in hypertensive patient. In Ayurveda references no proper description of hypertension is available. By viewing the pathogenesis and physiology, it is formed by the involvement of Tridoshas, Srotorodha, and Dhatudushti. The present case is a 60-year male patient was diagnosed uncontrolled hypertension with microalbuminuria, admitted for 1month, presented with complaints such as frothy urine, over tiredness, uncontrolled anger and increased blood pressure during evening time, not controlled by hypertensive modern medicines. His urine albumin-creatinine ratio was 106.98 mg/dl of creatinine, microalbumin in urine 138 mg/dl and uric acid was 11.5 mg/dl. He was advised the internal Ayurveda medicines, diet restriction and yogic breathing exercise. Within one month of treatment the urine albumin creatinine ratio and uric acid was reduced and became normal. His blood pressure also became controlled and recovered all symptoms. Ayurvedic treatment module appears to be safe and efficacious with early recovery and better outcomes in this case.